The Effect of Digital Work Environment on Online Driver Engagement in Indonesia - Kosasih, Nico (TechTalent & Business Review, 2025)
This study aims to analyze the effect of the digital work environment on online driver employee engagement in Indonesia. The rapid digital transformation has shifted work patterns toward application-based systems, requiring effective online communication, flexible scheduling, and stable technological support. This research employed a quantitative approach with an explanatory design. The sample consisted of 150 online drivers selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression with SPSS software. The results show that the digital work environment has a positive and significant effect on online driver engagement (B = 0.452; p < 0.001; R² = 0.285). This indicates that the better the quality of the digital work environment reflected in application stability, transparency of incentive systems, effective digital communication, and flexible working hours the higher the level of engagement among online drivers. A well-managed digital work environment can enhance motivation, loyalty, and a sense of belonging toward the platform. This study reinforces the Job Demands Resources (JD-R) and Self-Determination Theory (SDT) frameworks, suggesting that digital work resources can improve engagement when supported by organizational commitment and digital well-being. The findings provide practical implications for application-based companies to strengthen their digital infrastructure and implement flexible work policies to improve both engagement and the digital well-being of their driver partners.